The Relationships between Tax Shield and Capital Structure: In the Case of the Mongolian Listed Companies (Journal of Finance, Business and Management Studies, 2024)
Abstract It is common for companies to use depreciation expense of fixed assets and interest expense, regarding the cost of long-term liabilities, as a tax shield to reduce the impact of the tax burden. Many researchers have verified that it has a certain effect on the capital structure. Financial statements of 20 listed companies at the Mongolian Stock Exchange covering the 2016-2020 years were analyzed to study the relationships between capital structure and tax protection. Depending on the research model, the debt-to-asset ratio was selected as a dependent variable, and the effective tax rate- an indicator of debt tax protection and depreciation expense - an indicator of non-debt tax protection were selected as independent variables respectively. As control variables, indicators such as enterprise size, capital structure, return on capital, capital growth, cash flow, turnover ratio, and bankruptcy risk were considered. In order to perform the research analysis the MS-Excel and SPSS 25.0 software were used as research tools. According to the research results, capital structure is negatively related to debt tax and non-debt tax shield, which need extra analysis. Therefore, there was a categorized analysis following the shareholder register was conducted to verify the research purpose. The result has demonstrated that companies categorized in II have somewhat more impact of tax shield on the companies’ debt-to-asset ratio.
Keywords: tax protection, asset structure, tax shield effect, asset-liability ratio